Pengaruh Strategi Penerapan E-Procurement Terhadap Pencegahan Fraud Pengadaan Barang dan Jasa dengan Sistem Pengendalian Internal Sebagai Variabel Moderasi Pada PT PNM - Saefudin, Ence Dindin; Suharto, Eduardus (Jurnal Indragiri Penelitian Multidisiplin, 2025)
This research aims to analyze the influence of e-procurement strategies on preventing fraud in goods and services procurement with internal control systems as a moderating variable at PT Permodalan Nasional Mandiri (PNM). The complexity of fraud in goods and services procurement is the primary focus, where e-procurement is viewed as a strategic instrument to minimize fraud risks. The study employs an explanatory quantitative approach using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) method. The research population comprises 80 employees of PT PNM directly involved in goods and services procurement processes. Sampling was conducted using a saturated sampling method, where the entire population served as the research sample. The studied variables include e-procurement strategy as the independent variable, fraud prevention as the dependent variable, and internal control system as the moderating variable. Research findings demonstrate that e-procurement strategy has a positive and significant effect on fraud prevention, with a p-value of 0.001. The internal control system was proven to significantly moderate the relationship between e-procurement and fraud prevention. The research confirms that comprehensive e-procurement implementation, supported by a robust internal control system, can effectively reduce fraud risks in goods and services procurement. The study provides theoretical contributions to developing a technology-based fraud prevention model and offers practical recommendations for PT PNM management to optimize procurement strategies that are transparent, accountable, and integrity-driven.